Geomechanical factor of the intake of additional capacities of free methane at the exploitation of gas deposits - Bulat, A.F.; Lukinov, V.V.; Bezruchko, K.A.; Krukovskyi, O.P.; Krukovska, V.V. (Reports of the National Academy of Sciences of Ukraine, 2018)
The hypothesis of forming a fracture-porous structure of secondary rocks on the gas-deposit development as a result of a decrease of the gas pressure and the development of compression deformations in a productive re- servoir, which stipulate deformations of tension in a low-porous reservoir, assisting the redistribution of water and the gas, and forming the technogenic reservoir in it, is proposed. A mathematical model for the simulation of processes occurring at the development of a gas deposit is developed. The numerical simulation of changes of geomechanical and filtration parameters for the test model of a gas deposit is executed. It is shown that the con- siderable decrease of the gas pressure at the long-term exploitation of a deposit stipulates the deformation of higher- and underlying rock strata. The enhanced variability of the stress field creates an increase in the permeability near-by a layer-reservoir at the reserve depletion of hydrocarbons. If there is a low-porous reservoir in the area of enhanced variability, its gas recovery will grow, being conditioned by an increase in the permeability.